The civil liability of the consortium members for the individual mistake of one member - M. Elsawi, Ahmed (International Journal of Engineering and Technology, 2018)
Nowadays, the various forms of contractual agreements have spread between the different contracting companies for the purpose of executing the huge international contracts which require the synergy of all efforts. This has led to the appearance of new forms of cooperation between the international contractors, called the "Consortium Agreement", which is a kind of special partnership entered into for the purpose of executing a certain project, and ends at the completion of this project, without the constitution of a separate entity for the parties of this consortium. Nonetheless, many and various legal implications result from this consortium, some of which may be attributed to the subordination relationship between this agreement and the international contract of construction; while other legal implications might be attributed to the Consortium Agreement itself. The main problem in this regard may arise, if the consortium members did not agree on the accurate determination of the civil liability for each party, whether it was during the pre-contractual stage, or during the contract's execution; as well as the specific determination of the consortium members' liability towards the employer for the individual mistake of one member, especially in light of the multiple parties and the unity of purpose. In this regard, the liability may take one of the following two forms: first, to consider all members of the consortium as joint partners before the employer; second, to adopt the personal liability of each member separately, thus, each member shall be liable only for the part assigned to him. Hence, we will try here to answer a major question regarding the liability of the consortium members for the individual error of one member towards each other or towards the employer, taking into consideration the special nature of the Consortium Agreement.Â Â